The Influence of Social Relationships on Conduct Problems in School Context - Does School Engagement Matter? - Lätsch, Alexander; Raufelder, Diana; Wulff, Tino (International Journal of Criminology and Sociology, 2016)
There has been an increase in the prevalence of problem behavior during adolescence over the last decades. Thereby, studies have found that social bonds and relationships as well as school engagement as a form of connectedness play an important protective role. However, less is know whether school engagement is as a potential mediator in the association of social relationships with peers and teachers and conduct problems. The current study examined this interplay in a large non-clinical sample of students (N= 1.088; MAge= 13.7 SD=0.53 at T1; N= 845; Mage = 15.32, SD = .49 at T2) in secondary schools in Brandenburg, Germany. Structural Equation Modeling (SEM) was used to test the mediating effect from school engagement in the association between students’ social relationships in early adolescence and conduct problems in middle adolescence. The results show that school engagement function as full mediator in the association of both student-student relationships and teacher-student relationships at T1 and conduct problems at T2. This highlights that fostering school engagement in early adolescence might be an essential starting point for prevention and intervention strategies of conduct problems in middle adolescence.